RESEARCH ON IMPACT LOADING OF A MOBILE TRACKED PLATFORM WITH AN AUTONOMOUS STABILIZATION SYSTEM - TKACHUK, ANDRII; GROMOVYI, OLEKSIY; BEZVESILNA, OLENA; BONDARCHUK, VASIL (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The work presents a developed 3D model of a mobile robotic platform with an autonomous stabilization system for reconnaissance operations. Mobile robotic platforms have been found to be widely used in intelligence because they can help gather information from dangerous and hard-to-reach places and reduce the risk to the lives of intelligence personnel. Unmanned aerial vehicles and mobile robotic platforms with tracks are mainly used in reconnaissance. An important distinguishing quality of tracked mobile robots is their maneuverability. Having an independent drive for each of the tracks separately, the mobile robot can easily change the direction of its own movement. A study on shock loads (external influences on the system that can cause deformation, damage or destruction) of a mobile tracked platform with an autonomous stabilization system was conducted and the obtained results were described. The SOLIDWORKS software environment was used to model the design of the mobile platform. For numerical studies on impact loads, it is advisable to use linear elastic isotropic materials and bilinear Mises plastic materials. The results of the simulation of the movement of the mobile platform of the developed structure and the stresses in the collision with different speeds of 1, 5, 10, 25 m/s and the platform material carbon steel and rubber are presented. It was established that when a mobile platform collides with speeds of up to 25 m/s, the maximum stresses do not exceed 1.85 MPa, which gives a sufficient margin of strength in the event of impact loads for the selected material of the mobile platform. The use of steel inserts allows you to reduce the value of the maximum contact stresses under impact load, but increases the cost of the mobile platform, increases the total weight and, accordingly, reduces the operating time from the installed power batteries.
Keywords: robotics; mobile platform; stabilization; shock loads; 3D model; reconnaissance; modeling